Is Housing Wealth An 'ATM'? : The Relationship Between Household Wealth, Home Equity withdrawal, and Saving Rates - Klyuev, Vladimir (IMF Working Papers; Working Paper ;, 2006)
This paper examines the role increasing personal wealth and home equity withdrawal (HEW) have had in the decline in the personal saving rate in the United States. It does so by comparing the U.S. experience with those of Australia, Canada, and the United Kingdom. Mortgage market liberalization and innovation should reduce household cash flow and collateral constraints while making housing wealth more liquid as HEW becomes easier over time. Regression analysis indicates the expected negative relationship between U.S. saving and net worth, with a somewhat smaller coefficient than in previous studies. HEW is estimated to have a temporary negative impact on saving of the order of 20 cents on the dollar.